[in vain] : performing her for herself : a thesis in partial fulfilment of the requirements for a degree of Masters in Design at Massey University, Wellington, NZ - Frauenstein, Meggan (Massey University, 2010)
Drawing on the language of the mirror and symbolism conventionally employed to describe the feminine myth, this project explores the daily performance of being ‘woman’ as influenced by the polemics of feminism and popular culture. “Performing Her for Herself” presents a feminism that interrogates the music video and contemporary ‘pop divas’, to encourage a feminist sensibility that allows for new ways of seeing, dually aware and embracing of the many and varied representations of ‘femaleness’. The project is structured around the tropes of representation, reflection and refraction: The Represented Social Body, the Reflective Historical Body and the Refracted Performing Body. Judith Butler and Henry Giroux furnish a theoretical context, providing speculative strategies of gender performance, notions of desire and the imaging of women. Embodied research considers not only the relationship between the viewer and the viewed but also the formal qualities of video, the screen envisaged as mirror. What begins as the daily performance of me for myself is refracted to consider the mythological body, temporality, seduction and a desperate vanity of perception in the performance of her for herself.
Appendices (Design gestures ; Exhibition footage) consisting of QuickTime files on CD-ROM not loaded but available with the hard copy
Keywords: Feminism in art; Femininity in art; Performance art; Meggan Frauenstein